Meningkatkan Prestasi Belajar IPA melalui Penerapan Metode Round Table Masa Pandemi Covid-19 pada Siswa Kelas VIII-B SMPN 1 Sukamulia - Nazir, Muhamad (Lembaga Yasin AlSys, 2021)
The purpose of this study was to determine the increase in science learning achievement through the application of the round table method. The subjects of this study were 31 students of Class VIII-B SMPN 1 Sukamulia in the academic year 2020/2021, consisting of 15 male students and 16 female students. The type of research used is Classroom Action Research (CAR) with the class action process carried out in 2 cycles, consisting of 4 continuous stages, namely: (1) planning, (2) implementation, (3) observation, and (4) reflection. Data about learning activities were collected using observation techniques and data about student learning outcomes were collected from the results of the learning evaluation held at the end of each cycle and then analyzed using the rubric of the rating scale and also analyzed qualitatively and quantitatively by the researcher. The performance indicator in this study is that the research is said to be successful, if every student who takes the test reaches a minimum KKM of 70 and the percentage of students who succeeds in achieving a minimum KKM of 85%. Based on the results of research that has been carried out for two cycles, by the observer and the entire discussion as well as the analysis of student learning outcomes that have been carried out by the researchers themselves, it can be concluded that the first cycle of learning outcomes with classical completeness is 65% and the average value is 72.58 while the second cycle results studied with 87% classical completeness and an average score of 85.48. Thus the use of the round table method can improve science learning outcomes for class VIII-B students of SMPN 1 Sukamulia for the 2020/2021 school year.